Examining Fuel Use in Antiquity: Archaeobotanical and Anthracological Approaches in Southwest Asia - Smith, Alexia; Dotzel, Krista; Fountain, Joyce; Proctor, Lucas; von Baeyer, Madelynn (Ethnobiology Letters, 2015)
This article considers the study of wood and dung fuel use in antiquity across Southwest Asia by anthracologists and archaeobotanists. In recent years, the socially conditioned nature of fuel use has been highlighted and many scholars are stressing the central importance of fuel to pre-modern societies as on par with subsistence and tool use. By elevating and unifying the study of ancient fuel through anthracological, archaeobotanical, geochemical, and micromorphological studies, detailed insights into cultural practices, decision making, and resource use in the past can be gained. We provide a brief review of studies examining ancient fuel use and reflect on the integration of wood and seed data where seed assemblages are indicative of dung fuel use.